Assessment of Physical Health Status of Governmental High Schools' Male Students at Some Educational Areas of Tehran - Mahfoozpour; Ghorbani; Nooritajer; Akbarzadeh-baghban (Iran University of Medical Sciences, 2009)
Background and Aim: Teenagers and adolescents are considered as the future parents and responsibles therefore, their health status is of great importance and must be taken into consideration to prevent fore coming problems. The main purpose of this study was to assess physical health status of 14-18 years old high school male students at some educational districts in Tehran, Iran at 2006.   Material and Method: In this descriptive study, variables included assessment of physical growth (height weight), health status of vision, hearing, mouth and tooth, as well as vertebral column. Two hundred and sixteen boys aged between 14-18 years, from 36 high schools, were assessed after selection by multistage random sampling. The data collection tools consisted of a questionnaire and observation record sheets.   Results: The median values for weights and heights of the students (except for one group) were higher than the median point of N.C.H.S. In comparison to the N.C.H.S percentiles, the weights of 59.7% and the heights of 51.4% of the subjects were between percentiles 50 to 97.   The findings showed that 21.3% of the students had astigmatism in one or both eyes, 4.2%, had hearing loss in one or both ears, 69% had a decay in their permanent teeth, and the average DMFT was 3.44±23.72, and 8.8%, 2.8% and 6.9% of the students had scoliosis, lordosis and k i phosis respectively. The relationship of the fathers education and the number of children in the family with DMFT index were statistically significant (p<0.05).   Conclusion: The present study shows the importance and necessity of focusing on more prevalent physical disorders (such as oral health, mal-nutrition, vision & skeletal status) in boy's high schools and applying simple screening procedures, referrals and emphasizing their importance to the authorities.